2018
DOI: 10.1021/acs.est.8b05015
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenation Prevents Arsenic Mobilization during Deepwell Injection into Sulfide-Bearing Aquifers

Abstract: Coal seam gas (CSG) extraction generates large volumes of coproduced water. Injection of the excess water into deep aquifers is often the most sustainable management option. However, such injection risks undesired sediment–water interactions that mobilize metal­(loid)­s in the receiving aquifer. This risk can be mitigated through pretreatment of the injectant. Here, we conducted a sequence of three push–pull tests (PPTs) where the injectant was pretreated using acid amendment and/or deoxygenation to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 34 publications
0
48
1
Order By: Relevance
“… The first scenario involved the deoxygenation of the injectant to suppress pyrite oxidation, as recently proposed (e.g., Prommer et al, 2018) to prevent arsenic mobilization during (re)injection of coal seam gas coproduced water into the Precipice aquifer in Queensland, Australia. In this scenario, dissolved oxygen concentrations in the injectant were assumed to be zero, while all other water quality parameters were left similar to the current injectant composition. The second scenario simulates the amendment of bicarbonate with the aim of enhancing the pH buffering capacity of the injectant (e.g., Robinson et al, 2009).…”
Section: Potential For Injectant Manipulation To Safeguard Water Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“… The first scenario involved the deoxygenation of the injectant to suppress pyrite oxidation, as recently proposed (e.g., Prommer et al, 2018) to prevent arsenic mobilization during (re)injection of coal seam gas coproduced water into the Precipice aquifer in Queensland, Australia. In this scenario, dissolved oxygen concentrations in the injectant were assumed to be zero, while all other water quality parameters were left similar to the current injectant composition. The second scenario simulates the amendment of bicarbonate with the aim of enhancing the pH buffering capacity of the injectant (e.g., Robinson et al, 2009).…”
Section: Potential For Injectant Manipulation To Safeguard Water Qualitymentioning
confidence: 99%
“…The oxidation of ferrous to ferric iron was simulated following a previously established rate expression (Eckert & Appelo, 2002;Sun et al, 2018). The iron(III) produced from the reaction was allowed to precipitate as Fe(OH) 3 , which was modeled as an equilibrium reaction (Prommer et al, 2018;Sun et al, 2018). Seibert et al (2016) suggested that in response to acidity generation, proton buffering was the major pH buffering process during the GWRT.…”
Section: Water Resources Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…These conditions favor the reductive dissolution of Fe-oxides/hydroxides, releasing associated As into porewater [22]. Aqueous As concentrations can also increase due to the oxidation of As-bearing iron sulphide minerals, such as pyrite or arsenopyrite [23,24].…”
Section: Introductionmentioning
confidence: 99%